Review of Patent Infringement Litigation in the People’s Republic of China - Jianyang, Yu (Columbia Journal of Asian Law, 1991)
As the Patent Law of the People’s Republic of China (P.R.C.) enters its seventh year of existence since promulgation in 1985, the patent system in the P.R.C. is proving to be quite a success. Two contributing factors to its success are the increase in the number of patent applications and the commercialization of patented technology. According to statistics from the Patent Office, the number of patent applications has been increasing by an average of about 24% per year, and in 1990, the production value of 3,518 patents in use added about RMB 6.27 billion yuan (U.S. $1.17 billion). If, however, the Patent Law is not effectively and fairly enforced by courts, the whole patent system will be crippled. Hence, whether and how effectively Chinese courts enforce the Patent Law as well as handle patent infringement litigation have become issues of primary concern in both the P.R.C. and abroad. According to the Supreme Court’s statistics, up to the end of 1990, courts had received 449 patent lawsuits, among which about 65 percent were patent infringement cases.